PERANCANGAN SISTEM INFORMASI CUTI KARYAWAN BERDASARKAN SIKLUS HIDUP PENGEMBANGAN SISTEM DI UNIVERSITAS DIRGANTARA MARSEKAL SURYADARMA - Muryan Awaludin; Jehan Saptia Kurnia (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2023)
AbstractThe application of the manual method for managing leave application data has several obstacles that result in less efficiency and effectiveness at work, so based on these conditions a system is needed that can assist the activity of managing employee leave requests, so that a system development life cycle is needed or commonly called SDLC (System Development Life). Cycle) in managing computerized leave requests starting from the activity of submitting leave to the approval process which can be done online. The results of the questionnaire tabulation carried out by the author produced a fairly high level of satisfaction, which was calculated using a scale of 5 values Performance = 3.96, Information and data = 3.68, Economic = 3.80, Control and Security = 3.84, Efficiency = 4.14, and Service = 3.89.Â Keywords: Leave Information System, CodeIgniter, SDLC